2021
DOI: 10.3390/toxics9020028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sub-Lethal Doses of Selenium Nanoparticles on the Health Status of Rats

Abstract: Selenium nanoparticles (SeNPs) are fast becoming a key instrument in several applications such as medicine or nutrition. Questions have been raised about the safety of their use. Male rats were fed for 28 days on a monodiet containing 0.5, 1.5, 3.0 and 5.0 mg Se/kg. Se content in blood and liver, liver panel tests, blood glucose, total antioxidant capacity (TAC), the activity of superoxide dismutase (SOD) and glutathione peroxidase (GPx) were analysed. Liver and duodenum were subjected to histopathology examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Other experiments on mice and rats supplemented with SeNPs demonstrated the hepatotoxic effect of SeNPs, which were also confirmed by further histological examination [47,62,137,138,142]. Damage to the liver parenchyma and intestinal epithelium in rats was reported after 0.5, 1.5, 3, and 5 mg/kg DM of SeNP supplementation [136]. The authors suggest that short-term SeNP supplementation can be safer and more beneficial in specific treatments.…”
Section: No Toxic Effect In Tissues Occurredmentioning
confidence: 52%
“…Other experiments on mice and rats supplemented with SeNPs demonstrated the hepatotoxic effect of SeNPs, which were also confirmed by further histological examination [47,62,137,138,142]. Damage to the liver parenchyma and intestinal epithelium in rats was reported after 0.5, 1.5, 3, and 5 mg/kg DM of SeNP supplementation [136]. The authors suggest that short-term SeNP supplementation can be safer and more beneficial in specific treatments.…”
Section: No Toxic Effect In Tissues Occurredmentioning
confidence: 52%
“…In the context of experimental animal exposure to selenium nanoparticles (Se NP), several studies have reported varied changes in body weight when compared to control groups. Specifically, decreases in body weight were observed in some studies (Hadrup et al, 2019;He et al, 2014;Urbankova et al, 2021;Wang et al, 2007;Zhang et al, 2005Zhang et al, , 2008, while other studies reported no changes (Hadrup et al, 2016) (Table 2). Notably, the absence of changes in body weight in response to a dose of 0.5 mg Se NP/kg reported by Hadrup et al (2016) cannot be solely attributed to low dose exposure or the absence of intoxication, since decreases in body weight were observed at doses of 0.05 mg/kg Se NP (Hadrup et al, 2016) and 2 (Bhattacharjee et al, 2019), 20 mg/kg Se NP (Shakibaie et al, 2013), and 5 mg Se/kg food (Benko et al, 2012), but not at doses of 0.2, 0.4, 0.5, 2.5, 5, and 10 mg Se NP/kg (Hadrup et al, 2016(Hadrup et al, , 2019He et al, 2014;Shakibaie et al, 2013).…”
Section: Body Weightmentioning
confidence: 97%
“…Several studies have investigated the impact of selenium on liver function and histology. While some studies have reported an increase in alanine aminotransferase (ALT) activity (Wang et al, 2007;Zhang et al, 2005Zhang et al, , 2008, others have observed a reduction (Urbankova et al, 2021;Zhang et al, 2019) or no change in ALT activity (He et al, 2014). As for aspartate aminotransferase (AST) activity, some studies reported no change (Shakibaie et al, 2013;Urbankova et al, 2021;Zhang et al, 2005), while others reported an increase (He et al, 2014) or a decrease (Zhang et al, 2019).…”
Section: Livermentioning
confidence: 99%
“…It has diverse antioxidant and pro-oxidant actions based on dosage, duration, and oxidation state [ 104 ]. The use of SeNPs significantly reduces the death brought on by acute Se toxicity in a mouse model by up to four times [ 105 ]. Hepatotoxic indicators also demonstrate that SeNPs considerably reduce the liver damage caused by high dosages of Se [ 106 ].…”
Section: Selenium Nanoparticles (Senps)mentioning
confidence: 99%